The Brotherhood Medical Center: Collaborative Foundation of Maternity and Children’s Healthcare Facility for Displaced Syrians - Aburas, Rahma; Najeeb, Amina; Baageel, Laila; Mackey, Tim K. (Frontiers in Public Health, 2018)
The United Nations has declared the Syrian conflict, with more than 50% of Syria's population currently displaced, as the worst humanitarian crisis of the 21st century. The Syrian conflict has led to a collapse of infrastructure, including access to critical and lifesaving healthcare services. Women and children account for approximately 75% of internally displaced Syrians and refugees. This population is also particularly vulnerable to poor health outcomes, a condition worsened by lack of access to maternal and child health (MCH) services. In response to this crisis, a partnership of Saudi and Syrian physicians established a non-profit healthcare facility named the Brotherhood Medical Center (BMC) to serve women and children within a safe area near the Syrian -Turkish border. The project began in September 2014 and was implemented in three phases of establishment, phased construction and formal launch and operation. Currently, the BMC is working at about 70% of its capacity and is run in partnership with the Syrian Expatriate Medical Association (SEMA). Although there was strong initial support from donors, the BMC continues to face many financial and operational challenges, including difficulties in transferring money to Syria, shortage of medical supplies, and lack of qualified medical personnel. Despite these challenges, the BMC represents a critical model and an important case study of the challenges of delivering healthcare services to underserved populations during an ongoing conflict. However, more robust support from the international community is needed in order to ensure it continues its important health and humanitarian mission.